Potensi Desa Jambu Menuju Pengembangan Desa Wisata di Kabupaten Bengkulu Tengah - Putri, Novi Tri; Nopiah, Ririn; Izharudin, Izharudin (UNIB Press, 2024)
Jambu Village is one of the villages in Merigi Kelindang District, Central Bengkulu Regency. This village borders Penembang Village, which is one of the main tourist villages in Bengkulu Province. In efforts to develop and build a village, of course it cannot be separated from the village's potential. Mapping village potential is very important so that the implementation of village development can be in accordance with local characteristics and provide maximum results. The community service activities that will be carried out by the team from the Master of Applied Economics FEB Bengkulu University aim to explore and map the potential of Jambu Village regarding the development of tourist villages. The results of community service show that more than 50% of activity participants know and understand the socialization material about village potential for developing tourist villages in Jambu Village.